Towards Autonomous Uwb-Based Uav Indoor Navigation - Krupáš Maroš; Pačuta Kristián; Zolotová Iveta (Acta Electrotechnica et Informatica)
This paper presents a system for autonomous indoor navigation of the DJI Mini 3 drone by combining an Android-based control application with ultra-wideband (UWB) technology for precise localization. The development process involved two main phases: (1) enabling drone control and sensor access through the DJI Mobile SDK and (2) integrating UWB-based positioning data for reliable indoor navigation. Three autonomous navigation methods were designed and evaluated, each leveraging UWB data to a different extent. The results demonstrate that incorporating UWB significantly improves positioning accuracy for our solution compared to relying solely on the drone’s built-in sensors. Overall, this work highlights the potential of UWB technology to enhance drone operations in environments where GPS is unavailable, paving the way for advanced applications in indoor logistics, monitoring, and other industrial or service-oriented scenarios.